Mi sueño de América - Gallegos, Yuliana; Baeza, Georgina; Gallegos, Yuliana; Gallegos, Yuliana (Houston, Texas : Piñata Books, 2007)
Yuliana recalls her move from Monterrey, Mexico, to Houston, Texas, and describes her experiences as an immigrant child in her new environment.
Online resource; title from ePub and PDF title page (Digitalia, viewed June 13, 2014)
Keywords: Mexican Americans -- Texas -- Houston -- Juvenile literature; Mexican Americans -- Juvenile literature; Mexico -- Emigration and immigration -- Juvenile literature; United States -- Emigration and immigration -- Juvenile literature; Electronic books